High‐Throughput Analyses of Glycans, Glycosites, and Intact Glycopeptides Using C4‐and C18/MAX‐Tips and Liquid Handling System. Issue 7 (7th July 2021) - Chen, Shao‐Yung; Clark, David J.; Zhang, Hui
Abstract: Protein glycosylation is one of the most common and diverse modifications. Aberrant protein glycosylation has been reported to associate with various diseases. High‐throughput and comprehensive characterization of glycoproteins is crucial for structural and functional studies of altered glycosylation in biological, physiological, and pathological processes. In this protocol, we detail a workflow for comprehensive analyses of intact glycopeptides (IGPs), glycosylation sites, and glycans from N‐linked glycoproteins. By utilizing liquid handling systems, our workflow could enrich IGPs in a high‐throughput manner while reducing sample processing time and human error involved in traditional proteomics sample processing techniques. Together, our workflow enables a high‐throughput enrichment of glycans, glycosites, and intact glycopeptides from complex biological or clinical samples. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Enzymatic digestion of glycoproteins using C4‐tips Basic Protocol 2 : Intact glycopeptide analysis using C18/MAX‐tips Basic Protocol 3 : Glycan and glycosite analysis